2014
DOI: 10.1038/bjc.2014.76
|View full text |Cite
|
Sign up to set email alerts
|

Tumour biomechanical response to the vascular disrupting agent ZD6126 in vivo assessed by magnetic resonance elastography

Abstract: Background:Magnetic resonance elastography (MRE) is an emerging imaging technique that affords non-invasive quantitative assessment and visualization of tissue mechanical properties in vivo.Methods:In this study, MRE was used to quantify (kPa) the absolute value of the complex shear modulus |G*|, elasticity Gd and viscosity Gl of SW620 human colorectal cancer xenografts before and 24 h after treatment with either 200 mg kg−1 of the vascular disrupting agent ZD6126 (N-acetylcolchinol-O-phosphate) or vehicle con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 29 publications
4
41
0
Order By: Relevance
“…In a more recent study, it has been observed that malignant liver tumors are mainly characterized by increased viscosity [128]. Small animal studies have shown that MR elastography is useful for assessing the early tumor response to vascular disrupting agents and to chemotherapy [129][130][131]. Further human trials are needed to clarify the role of multi-frequency MR elastography in characterizing liver tumors and assessing their response to treatment.…”
Section: Diffuse Liver Diseasesmentioning
confidence: 99%
“…In a more recent study, it has been observed that malignant liver tumors are mainly characterized by increased viscosity [128]. Small animal studies have shown that MR elastography is useful for assessing the early tumor response to vascular disrupting agents and to chemotherapy [129][130][131]. Further human trials are needed to clarify the role of multi-frequency MR elastography in characterizing liver tumors and assessing their response to treatment.…”
Section: Diffuse Liver Diseasesmentioning
confidence: 99%
“…Histological analysis showed decreased levels of cellular proliferation in chemotherapy treated tumors. Another preclinical study by Li et al [20] evaluated MRE derived stiffness in human colorectal carcinoma cells, which were implanted subcutaneously in the flanks of genetically modified mice. MRE was performed before and 24h after treatment with either the vascular disrupting agent ZD6126 (N-acetylcolchinol-O-phosphate) or vehicle control.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that change in TS may antecede actual cell death as indicated by histology, and that decreasing cellularity may contribute to the change in tissue mechanical properties [20]. This would potentially allow us to use stiffness as a biomarker of treatment response and also to longitudinally monitor treatment response throughout the course of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Investigations of therapy-induced changes in tumor stiffness have continued in the preclinical setting, where Li et al found a significant decrease in bulk stiffness as assessed by magnetic resonance (MR) elastography 24 h after administration of a vascular disrupting agent in a murine model of breast cancer. 28 Interestingly, elasticity was seen to exhibit significant changes at this early imaging time point while another quantitative imaging biomarker, the apparent diffusion coefficient from diffusion-weighted MR imaging, did not. Pepin et al have also used MR elastography to assess therapy-induced changes in tumor stiffness and have shown a significant decrease in stiffness in response to cytotoxic therapy in a murine lymphoma xenograft model.…”
Section: Introductionmentioning
confidence: 92%